STRUCTURAL MICRO-STUDIES ON THE DISCOURSE OF THE INDONESIAN DIGITAL NATIONAL DAILY NEWS MAY 2024 EDITION - Andriani, Margareta; Emawati; Ameliza Malay, Ayu; Pebrika, Audi (Jurnal Ilmiah Bina Bahasa, 2025)
The purpose of this study is to describe in depth several aspects of grammatical and lexical tools contained in the discourse of the May 2024 edition of the Indonesian Digital National Daily  News, to describe the aspects of grammatical tools and the dominant lexical device aspects, and to describe the types of tools whose emergence has great intensity in the Discourse of the  Indonesian Digital National Daily News May 2024 edition. The data analysis in this study uses the distribution method. This method is used to describe several aspects of grammatical tools and some aspects of lexical tools contained in the Discourse of the May 2024 edition of the Indonesian Digital National Daily News. Furthermore, with this method, it can also be illustrated with the aspect of grammatical tools and the dominant aspects of lexical tools, and the types of tools whose appearance has great intensity in the discourse of the May 2024 edition of the Indonesian Digital National Daily News. The approach used in this study is a microstructural approach. The microstructural approach is an approach that examines discourse based on aspects of form and aspects of meaning. It can be further explained that the form aspect is a structure born of language that includes grammatical aspects. The meaning aspect is the inner structure of a language that includes the lexical aspect.